Exploring the barriers for people taking protective actions during the 2012 and 2015 New Zealand ShakeOut drills. (July 2019) - McBride, Sara K.; Becker, Julia S.; Johnston, David M.
Abstract: To reduce future earthquake injuries and casualties, it is important that people understand how their behavior, during and immediately following earthquake shaking, exposes them to increased risk of injury or death. Research confirms that protective actions can reduce injuries and that prior training can help prepare people to take appropriate actions. In this paper, we examine barriers to participation in the ShakeOut drills in New Zealand. Through citizen science research, volunteers observed people performing the drills in 2012 and 2015. Observers reported how long it took to perform the drill and why they thought some people may not have completed it. Our findings illustrate that children, elderly, and those with both mental and physical disabilities struggled with the drill. Furthermore, embarrassment was a reported leading cause for non-participation; we recommend more inclusive messaging to address potential causes of embarrassment.